2023
DOI: 10.1002/anie.202304700
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Functionalization with Carbon Dioxide and Carbon Disulfide Giving Symmetric and Unsymmetric Hydrazido Complexes

Abstract: Here we show that a tridentate bis(aryloxide)anilide-ligated titanium/potassium scaffold promotes functionalization of coordinated N 2 with CO 2 and CS 2 through formation of NÀ C bonds. Treatment of a naphthalene complex with N 2 gave an end-on bridging dinitrogen complex featuring a [Ti 2 K 2 N 2 ] core. The dinitrogen complex underwent insertion of CO 2 into each TiÀ NN bond to afford an N,N'-dicarboxylated hydrazido complex. Stepwise nitrogen-carbon bond formation at coordinated N 2 proceeded to afford an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…In principle, the addition of an activated N 2 unit to unsaturated organic substrates could offer an atom-efficient route for the synthesis of organonitrogen compounds. However, studies toward this goal remained limited despite great interest and recent advances. The nucleophilic addition of N 2 or N 2 -derived nitrido and imido species to unsaturated carbon-heteroatom bonds such as CO, CO 2 , ,, aldehydes/ketones, acid halides, nitriles, , and heteroallenes ,,,, has been reported. However, the addition reaction of N 2 with unsaturated C–C bonds has remained almost unexplored to date. , In particular, the addition of an N 2 unit to an α,β-unsaturated carbonyl compound through the C–N bond formation to produce an NN-functionalized organic compound has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the addition of an activated N 2 unit to unsaturated organic substrates could offer an atom-efficient route for the synthesis of organonitrogen compounds. However, studies toward this goal remained limited despite great interest and recent advances. The nucleophilic addition of N 2 or N 2 -derived nitrido and imido species to unsaturated carbon-heteroatom bonds such as CO, CO 2 , ,, aldehydes/ketones, acid halides, nitriles, , and heteroallenes ,,,, has been reported. However, the addition reaction of N 2 with unsaturated C–C bonds has remained almost unexplored to date. , In particular, the addition of an N 2 unit to an α,β-unsaturated carbonyl compound through the C–N bond formation to produce an NN-functionalized organic compound has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, N–C bond formation from linear end-on bridging dinitrogen is rare. 16,17 We previously reported the titanium dinitrogen complex [K(THF) 6 ][{(O 3 C)Ti} 2 (μ-N 2 ){K 3 (THF) 3 }] ( 1 ) ([O 3 C] 4− = [(3,5- t Bu 2 -2-OC 6 H 2 ) 3 C] 4− ), which displays a strongly activated N 2 ligand coordinated by two titanium metals in a linear end-on fashion as well as three potassium metals in a side-on fashion. Initial reactivity studies of 1 showed that the nucleophilic character of its dinitrogen unit can promote N–C bond formation with carbon-based reagents.…”
mentioning
confidence: 99%